Epidemiologia dos acidentes causados por Thalassophryne nattereri (niquim) no Estado do Ceará e Estudo dos efeitos do veneno em rim isolado - Facó, Patrícia Emília Gomes (2003)
The accident caused by the fish T. nattereri is responsible for a severe clinicai picture of pain, edema and necrosis at the site of the lesion. It Represents a serious medicai, economic and social problem in the Northeast of Brazil. Its venom is poorly studied and at this moment, there is no specific treatment for the accidents caused by this fish. The objectives of this work were to analyze the epidemiological aspects of the accidents caused by niquim in the Ceara State in the period 1992 to 2002 and also evaluate the renal effects through the dosage of sequence parameters related with the renal physiology and histological analysis of that organ. In the period of 1992 to 2002, 16 cases of envenomation by T. nattereri occurred in the seaside of Ceara and were registered at CEATOX- Toxicological Assistance Center in this State. The majority of the accidents (87,5%) happened on the beaches of Fortaleza, and only 12,5% occurred out of town. Men (94%) predominated over women, with ages (75%) between 21 to 40 years and 19% were 41 to 60 years old. The time medicai assistance from the accident varied from 1 to 5 hours (4 cases), from 6 to 12 hours (3 cases), abo ve 12 hours in 4 cases and 5 patients didn’t know inform the time between the accident and the medicai assistance. The clinicai picture more ffequent was pain, edema and also ischemia, local paralysis, echymoses and bumed skin sensation. Anti-inflammatory and analgesic drugs were used. In some cases, were used anesthetic, hot water, surgery wash and anti-histaminic. In 75% of cases cure was confirmed and 12% cure was not confirmed. Probably the number of the accidents is higher than it was found because the information system is not efficient. We used Wistar rats, weighing 220 a 270g, divided into 4 groups of 6 animais each. After the animais were anaesthetized with pentobarbital sodium (50mg/Kg), and right ureter was cannulated like as the upper mesenteric artery, without interruption of the vascular flow. The experiments lasted for 120 minutes and samples of urine and perfusate were colleted every 10 minutes for further biological analysis of inulin, sodium, potassium, chloride and osmolality. We tested three different doses (0,3pg/ml, lpg/ml and 3pg/ml) of T. nattereri fish venom for the evaluate of perfusion pressure (PP), renal vascular resistence (RVR), glomerular filtration rate (GFR), urinary flow (UF), sodium, potassium, and chloride tubular transport percentage (%TNa+, %TK+, %TC1), sodium, potassium, and chloride proximal tubular transport percentage (%pTNa+, %pTK+, %pTCl), sodium, potassium and chloride excretion (ENa+, EK+, EC1") and osmotic clearance (Cosm). We observed a significant increase (p<0,05) in the parameters of PP and RVR in all three concentrations used. There is a statistic growth in the GFR, UF, ENa+, EK+ e Cosm using 0,3 and lpg/ml at 90 and 120 minutes. The dose of 3pg/ml caused a significant decrease in the GRF, UF, %TNa+, %TK+, %TCf, %pTNa+, %pTCl‘, at 90 and 120 minutes, happening the same for this last parameter at 60 minutes in the doses of 0,3 and 3pg/ml. We found a significant increase in the ECE at the 90 minutes, and the %pTK+ and ENa+ at the 120 minutes. The %pTK+, EK+and ECF diminished after 90 minutes in the dose of 3pg/ml. Even though we found eosinofilic casts in the renal tubules and proteinaceous material in the urinary space no abnormalities were seen in the renal vessels. We conclude that the T. nattereri venom altered the renal physiology in the isolated kidney model interfering especially in the vascular parameters. The effects observed, probably were promoted by myotoxic agents or for the venom action in the renal cells causing the release of vasoative factors that could increase perfusion pressure and renal vascular resistance and decreases of electrolytes transport in higher doses.